A rhesus macaque model of α‐dystroglycanopathy caused by a POMT1 splice altering variant - Anya Nordlund; Brian LaMendola; Nathan P. Crilly; Seth Kittle; Betsy M. Ferguson; Anne D. Lewis; Jeff Wall; Samuel M. Peterson (Animal Models and Experimental Medicine, 2026)
Abstract Background Biallelic mutations in genes associated with α‐dystroglycan glycosylation manifest in a spectrum of conditions referred to as α‐dystroglycanopathies, including Walker–Warburg syndrome, which primarily disrupt brain, eye, and muscle development. While small‐animal models for the disease have been developed and described, the condition has not been documented in non‐human primates. Methods Three spontaneous cases of severe lissencephaly, microphthalmia, and congenital muscular contracture in infant rhesus macaques were investigated. Histological analysis was performed on brain, retina, and skeletal muscle tissue. Genomic sequencing and RT‐PCR were used to identify and validate the causative pathogenic variant. Results The genetic basis for disease was determined to be the result of a rare single nucleotide variant altering a canonical splice site in the POMT1 gene. Aberrant splicing was confirmed in affected monkeys and H&E staining demonstrated histological markers consistent with severe α‐dystroglycanopathy. Conclusions Recapitulation of this clinical disease phenotype in a non‐human primate establishes the utility of rhesus macaques as a model for dystroglycanopathies, such as Walker–Warburg syndrome.